Development of internet-based instrumentation for the study of hall effect - Abas, Ariffin; Shaari, Abdul Halim; Talib, Zainal Abidin; Abdul Wahab, Zaidan (Universiti Putra Malaysia Press, 2014)
The computer, together with Lab View software, can be used as an automatic data acquisition system. This project deals with the development of a computer interfacing technique for the study of Hall Effect and converting the existing automation system into a Web-based automation system. The drive board RS 217-3611 with PCI 6025E card and stepper motor RS191-8340 with a resolution of 0.1mm, was used to move a pair of permanent magnets backward and forward against the sample. The General Interface Bus (GPIB) card interfaces, together with digital nano voltmeter and Tesla meter using serial port RS232 interface, are used for measuring the potential difference and magnetic field strength respectively. Hall Effect measurement on copper (Cu) and tantalum (Ta) showed negative and positive sign Hall coefficient. Therefore, the system has electron and hole charge carriers respectively at room temperature. The parameters such as drift velocity, conductivity, mobility, Hall Coefficient and charge carrier concentration were also automatically displayed on the front panel of Lab View programming and compared with standard value. The Web-based automation system can be remotely controlled and monitored by users in remote locations using only their web browsers. In addition, video conferencing through Net Meeting has been used to provide audio and video feedback to the client